FACTORS AFFECTING KB ACCEPTORS IN THE SELECTION OF CONTRACEPTION EQUIPMENT IN WOMEN (IUD) IN MANDIRI PRACTICES PERA SIMALINGKAR B YEAR 2022 - Bernadetta Ambarita; Aprilita Sitepu; R Oktaviance S; Laura Rupana D (Sean Institute, 2022)
Contraceptives in uterus (IUD) can interpreted something type of family planning that has effectiveness height, and includes to in Method Contraception Long Term (MKJP). Effectiveness use (IUD) depending on the shape iud size iud, iud contain hormone / non- hormonal, as contraception effectiveness very high iud in its use is because failure in usage contraception it's very small. Destination researcher for describe factors which influence KB acceptor against election tool contraception in uterus (IUD). Method study descriptive, for describe factors KB acceptor about use tool contraception in uterus (IUD). sample as many as 30 respondents with accidental sampling technique sampling. Research location it's at Midwife practice Independent Pera on the moon may 2022. Research results prove of 30 family planning acceptors that influencing factors KB acceptor in election tool IUD contraception is factor majority knowledge found in knowledgeable enough as many as 13 respondents (43.3%), while the parity with the majority of multipara as many as 21 respondents (70%), on the Support husband with majority supportive husband as many as 19 respondents (63.3%), and the source information majority to power health as many as 13 respondents (43.3%). Can be concluded that factor knowledge, factor parity, factor Support husband and factor source information influence election tool contraception in uterus (IUD). because of that Support husband as well as source information provided by the staff health could support and motivate and amount the child born is also supportive existence knowledge KB acceptors that affect